Alat Dan Media Pembelajaran Dalam Perspektif Tafsir Al-Misbah - Gunawan, Gunawan; Pasaribu, Selamat (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2022)
Learning tools and media in Islamic education perspective). Every human being always undergoes a learning process throughout his life. The learning process is caused by the interaction between humans and their environment. For this reason, learning occurs whenever and wherever.